Study Protocol for Teen Inflammation Glutamate Emotion Research (TIGER) - Walker, Johanna C.; Teresi, Giana I.; Weisenburger, Rachel L.; Segarra, Jillian R.; Ojha, Amar; Kulla, Artenisa; Sisk, Lucinda; Gu, Meng; Spielman, Daniel M.; Rosenberg-Hasson, Yael; Maecker, Holden T.; Singh, Manpreet K.; et al. (Frontiers in Human Neuroscience, 2020)
This article provides an overview of the study protocol for the Teen Inflammation Glutamate Emotion Research (TIGER) project, a longitudinal study in which we plan to recruit 60 depressed adolescents (ages 13-18 years) and 30 psychiatrically healthy controls in order to examine the inflammatory and glutamatergic pathways that contribute to the recurrence of depression in adolescents. TIGER is the first study to examine the effects of peripheral inflammation on neurodevelopmental trajectories by assessing changes in cortical glutamate in depressed adolescents. Here, we describe the scientific rationale, design, and methods for the TIGER project. This article is intended to serve as an introduction to this project and to provide details for investigators who may be seeking to replicate or extend these methods for other related research endeavors.